NITRATE ACCUMULATION IN LETTUCE AND ROCKET IN RESPONSE TO NITROGEN FERTILIZATION IN INTERCROPPING - Barros Junior, Aurelio Paes; Cecilio Filho, Arthur Bernardes [UNESP]; Alves Rezende, Braulio Luciano; Lins, Hamurabi Anizio (Univ Fed Rural Semi-arido-ufersa, 2020)
In the cultivation of leafy vegetables, it is common to apply high amounts of nitrogen fertilizer. The imbalance between the absorption and the use of nitrogen (N) by the plant increases the nitrate content and decreases the quality of the vegetables because nitrate has a strong association with compounds harmful to human health. On the other hand, there is a lack of information on how N dose in intercropping, in order to improve yield, affects the quality (nitrate content) of vegetables. Thus, the objective of this study was to evaluate the nitrate content of intercropped lettuce and rocket, with nitrate content acting as a function of the nitrogen dose applied to these crops. The experiment was carried out at UNESP, Jaboticabal, SP, from September to December 2006. The experimental design was a complete randomized block design with four replications. The treatments were arranged in a 4 x 4 + 2 factorial scheme, with four varying concentrations of N each for lettuce and rocket (0, 65, 130 and 195 kg ha(-1) of N), plus two treatments corresponding to lettuce and rocket monocrops. Nitrate content in lettuce under intercropping is 42% less compared to that in the monocrop. Increasing nitrogen concentrations increased nitrate levels for lettuce and rocket under intercropping; however, these levels are below those found for their respective monocrops.
Keywords: Lactuca sativa; Eruca sativa; System of cultivation and nutritional quality